2020
DOI: 10.1021/acs.jpcc.0c06369
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and High-Temperature Thermochemistry of Oxygen-Deficient BaMO3 (M = Ti – Cu) Perovskites

Abstract: Alkaline-earth perovskites are of particular interest for high-temperature energy conversion processes because of their mixed-valence charge states, which significantly affect their chemical and thermal stability. However, in many cases, the thermochemical properties and stabilities of such perovskites under high-temperature conditions remain uncharacterized. We present here a systematic study of the stability, electronic structures, and thermochemical properties of oxygen-deficient BaMO3 (M = Ti – Cu) perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Zeng et al (Zeng et al, 2013) also found identical trends using RPBE in the predicted formation energies of cubic ABO 3 perovskites with alkali/rare-earth metals at the A site (Na, K, La) and 3d/5d transition metals at the B site (Ti-Cu, Ta, W, Re, Os, Ir, Pt). Furthermore, PBEsol has been employed to calculate the formation energies of cubic BaMO 3 (M = Ti À Cu) (Ghose et al, 2020), which shows consistency with the previous RPBE prediction ( Calle-Vallejo et al, 2010). Similarly, PBE-predicted formation energies of cubic ABO 3 perovskites (A = La, Be, Mg, Ca, Sr, Ba; B = Ti-Ni) show reasonable agreement with the experimental values (Su & Sun, 2015).…”
Section: Formation Energysupporting
confidence: 79%
See 4 more Smart Citations
“…Zeng et al (Zeng et al, 2013) also found identical trends using RPBE in the predicted formation energies of cubic ABO 3 perovskites with alkali/rare-earth metals at the A site (Na, K, La) and 3d/5d transition metals at the B site (Ti-Cu, Ta, W, Re, Os, Ir, Pt). Furthermore, PBEsol has been employed to calculate the formation energies of cubic BaMO 3 (M = Ti À Cu) (Ghose et al, 2020), which shows consistency with the previous RPBE prediction ( Calle-Vallejo et al, 2010). Similarly, PBE-predicted formation energies of cubic ABO 3 perovskites (A = La, Be, Mg, Ca, Sr, Ba; B = Ti-Ni) show reasonable agreement with the experimental values (Su & Sun, 2015).…”
Section: Formation Energysupporting
confidence: 79%
“…Notably, these temperature‐dependent enthalpic and entropic contributions are highly impacted by the oxygen non‐stoichiometry of ABO 3 perovskites. In our previous work, a comparison of entropic contributions between pristine and oxygen‐deficient BaMO 3‐δ (M = Ti–Cu) perovskites across the temperature range 0–2000 K, demonstrates that entropy values of pristine BaMO 3 have consistent increases with the increasing atomic number of B‐site cation from Ti to Cu (Ghose et al, 2020). However, oxygen vacancies in BaMO 3‐δ led them to deviate from this trend due to their unique phonon spectra impacted by the oxygen non‐stoichiometry (Ghose et al, 2020).…”
Section: Thermal Properties and Dft Uses For Perovskites In Stwsmentioning
confidence: 91%
See 3 more Smart Citations